¡Viejo del alma...! - Urdaneta Gómez, Roberto, 1955- (Editorial La Oveja Negra Ltda., 2015)
A compilation of articles written by the author in 1998 about the relationship between him and his father. A relationship, although sometimes seem traumatic, it had unfogettable moments.